PEMILIHAN MODA LANJUTAN PENGGUNA KERETA REL LISTRIK (KRL) DI STASIUN JUANDA, JAKARTA, INDONESIA - Rio Apriyanto; Lin Yola (DAS Institute, 2022)
This study aims to identify factors that influence KRL Users to choose the advanced mode of transportation used to reach their final destination. The method used in this study is quantitative and multinomial logistic regression. Calculations with multinomial logistic regression, in general, show slightly different results. In addition, trans-Jakarta public transportation modes tend to be more attractive to KRL users at Juanda Station for advanced modes of transportation. Some recommendations for determining continued travel with criteria for time, convenience, and cost, including 1) Pedestrians need to improve their comfort variables, so it is necessary to build better pedestrian paths. 2) Online motorcycle taxis need to build shelters/places to get on and off passengers in the Juanda station area to make it easier for users to use the online motorcycle taxi mode. 3) Transjakarta buses need to sterilize the Transjakarta route, considering the dense traffic on the road to the station, so there are no delays and queues on trans Jakarta buses. 4) Further studies need to be carried out on the other railway stations and need to be studied in more detail by paying attention to the variable level of service yang others.